The Collective Biography of Lithuanian Partisans’ Leaders - Žilytė, Enrika (Lietuvos istorijos studijos, 2017)
This article is devoted to the question that has not received many attention from historians so far: Can we find any similarities among the biographical details of Lithuanian partisan leaders? Prosopography has been chosen as the main method of this research, since it targets the common aspects of people’s lives, emphasizes the external similarities and differences between individuals within a particular population and in this way helps the researcher to reach the aim of a study.The biographies of the leaders were examined in several different aspects. First of all, the investigation of social aspects revealed that the most of the persons were born between 1910–1922; it implicates that they were born or grew in an independent state of Lithuania, where the nation and a patriotic attitude were seen as the values of first importance, plus the majority of the leaders originated from big farmer families that had resided in rural areas. In addition to this, their education and activities research showed that even 85% of them had a higher than primary education and about 60% shared something in common with the military: had completed a military school, taken their parts in compulsory military service, etc. The tendency of high activity in the military sphere could be noticed during the first Soviet and Nazi occupations, too. However, it is essential to add that only 35% of the leaders had acquired military ranks; therefore, it is not correct to state that the most of them were officers (this tendency could be observed in some historical works). Some of the partisans’ leaders were teachers, civil officers or farmers as well. During the Soviet and Nazi occupations, 68% of future leaders of the armed anti-Soviet resistance belonged to numerous underground resistance organizations, such as the Lithuanian Freedom Army, the Lithuanian Activist Front, or showed their disloyalty to the regime in some other ways. This gives us no doubt that their later decisions to join the partisans were consistent.An average duration of activity in the anti-Soviet partisan movement was between 2–3 years, while in comparison the leaders could stay alive for 6 years or more – this means that the leader must have been one of the most experienced individuals among other freedom fighters. The leader’s significant role in the battlefield as well as in the ideological area was undoubted and important, as we can discern from the special partisan military ranks and decorations given to a number of them during the anti-Soviet partisan war. The leaders’ efforts and the struggle for the freedom of the fatherland are highly estimated in independent Lithuania, too – 85% of them were awarded with high awards of the state. All in all, this article shows that these people had a lot of in common and we can actually discuss a quite solid and complete picture of the Lithuanian freedom fighters’ leader.
Keywords: anti-Soviet armed resistance; partisans; leaders; collective biography